2013
DOI: 10.4097/kjae.2013.65.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration pneumonia caused by fentanyl-induced cough -a case report-

Abstract: Although fentanyl-induced cough is generally transient and benign, it can give rise to serious problems in patients to whom increasing intracranial, intraocular or intraabdominal pressures may create dangerous situations. This case demonstrates aspiration pneumonia as a complication, exhibiting severe cough induced by intravenous injection of fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…On emergence from anesthesia, cough may protect against aspiration. However, cough can also result in perioperative morbidity, including tachyarrhythmia, arterial hypertension, cardiovascular collapse, and airway complications, [1][2][3][4][5][6][7][8][9] and it may increase intracranial, intraabdominal, and intraocular pressure. 10 An effective technique for preventing cough would be desirable in many situations where patients are at a particular risk.…”
mentioning
confidence: 99%
“…On emergence from anesthesia, cough may protect against aspiration. However, cough can also result in perioperative morbidity, including tachyarrhythmia, arterial hypertension, cardiovascular collapse, and airway complications, [1][2][3][4][5][6][7][8][9] and it may increase intracranial, intraabdominal, and intraocular pressure. 10 An effective technique for preventing cough would be desirable in many situations where patients are at a particular risk.…”
mentioning
confidence: 99%
“…The latter two studies Mukherjee et al (2011) from India, however, found an incidence rate of 59.8% while injecting fentanyl 2 μg/kg in 2 s, which indicated the injection time also played an important role. Lim et al (2013) from Korea reported that the literature suggests an incidence rate of FIC between 18.0% and 68.0%. Unfortunately, rare brand names and manufacturers of fentanyl were used in the above studies; therefore, we were not able to confirm whether the preservatives and other pharmaceutical components in fentanyl were the same across different reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, fentanyl intravenous injection can cause the so called fentanyl-induced cough (FIC) during the induction, which may be explosive or even life-threatening (He et al, 2016;Park et al, 2016). It is particularly dangerous for those patients suffering from airway diseases, acute upper airway obstruction, cerebral aneurysm, increased intracranial pressure, brain trauma, brain hernia, or dissecting aortic aneurysm, as severe FIC could lead to pneumothorax, optic nerve injury, or rupture of aneurysms (Lim et al, 2013;Saleh et al, 2014;Firouzian et al, 2015;Park et al, 2016;Peringathara and Robinson, 2016). In clinical settings, the reported incidence of FIC is variable (18.0%-74.4%) depending on the dosage, infusion speed, and route of administration (Sedighinejad et al, 2013;Solanki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…bolus administration of fentanyl or fentanyl-derived opioids can induce severe coughing in many patients. 17 This can be undesirable in patients at risk for aspiration, 14 with open globe eye injuries, or with increased intracranial pressure. Effective ways to prevent FIC include pretreatment with propofol, N-methyl--aspartate receptor antagonists, β 2 agonists, lidocaine, α 2 agonists, giving a small fentanyl dose 1-3 min before a larger fentanyl dose, or by slowing the rate of fentanyl injection.…”
Section: Discussionmentioning
confidence: 99%